The Activity Test of Dewandaru Fruit (Eeugenia uniflora L.) in Trachea of Male Mice (Mus musculus L.) Which Exposed to Cigarette Smoke - Antari, Ni Wayan Sukma (Jurnal Pijar Mipa, 2024)
Smoking has a serious negative impact on health because cigarettes contain harmful chemical compounds. To combat these negative effects, using natural antioxidants such as Dewadaru fruit has become the research focus. Dewandaru contains high antioxidants, namely flavonoids, anthocyanins, saponins, and tannins, which can fight free radicals in the body. The trachea is an air channel between the larynx and bronchi. To identify the activity test of dewandaru fruit (Eugenia uniflora L.) in the trachea of male mice (Mus musculus L.) exposed to cigarette smoke. This study employed true experimental di laboratory with post-test only control group design, probability sampling. The data were analyzed by using Shapiro Wilk and followed by the ANOVA test and Duncan's test. The finding showed that administering a Dewadaru fruit filter could maintain the histopathology of the male mice trachea exposed to cigarette smoke (P<0.05). Dewandaru fruit filter (Eugenia uniflora L.) has activity in the trachea exposed to cigarette smoke among male mice. Using a Dewadaru fruit filter also affects the presence of cilia, goblet cells, epithelial height, and lumen diameter in the trachea of male mice.